2023
DOI: 10.1101/2023.04.03.535331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimentally induced active and quiet sleep engage non-overlapping transcriptional programs inDrosophila

Abstract: Sleep in mammals is broadly classified into two different categories: rapid eye movement (REM) sleep and slow wave sleep (SWS), and accordingly REM and SWS are thought to achieve a different set of functions. The fruit flyDrosophila melanogasteris increasingly being used as a model to understand sleep functions, although it remains unclear if the fly brain also engages in different kinds of sleep as well. Here, we compare two commonly used approaches for studying sleep experimentally inDrosophila: optogenetic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Additionally, the effect observed during induced sleep was only observed in the central channels whereas the spontaneous sleep effects appear to at least cover the entire hemisphere from center to periphery. This shows that genetically-induced sleep in flies can produce strikingly different electrophysiological signatures than spontaneous sleep, consistent with several previous similar observations (Tainton-Heap et al 2021;Yap et al 2017;Anthoney et al 2023;Lin, Panula, and Passani 2015;Troup et al 2018). For the rest of this current study, we focus on spontaneous sleep.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the effect observed during induced sleep was only observed in the central channels whereas the spontaneous sleep effects appear to at least cover the entire hemisphere from center to periphery. This shows that genetically-induced sleep in flies can produce strikingly different electrophysiological signatures than spontaneous sleep, consistent with several previous similar observations (Tainton-Heap et al 2021;Yap et al 2017;Anthoney et al 2023;Lin, Panula, and Passani 2015;Troup et al 2018). For the rest of this current study, we focus on spontaneous sleep.…”
Section: Resultssupporting
confidence: 91%
“…This suggests that PEs occurring during sleep are qualitatively different from identical PE events occurring during wake. This suggests that the brain activity state (e.g., quiet or deep sleep (Tainton-Heap et al 2021;Anthoney et al 2023)) overrides the neural correlates associated with the same behavior occurring during wake.…”
Section: Lfp Features Of a Deep Sleep Stage With Proboscis Extensionmentioning
confidence: 99%
“…The fact that lower levels of mechanical stimulation failed to produce rebound over one full cycle, despite having produced similar amounts of sleep deprivation, suggests that high-frequency physical perturbation produces sleep-independent behavioral effects that might mask bona fide homeostatic sleep increases. Alternatively, it is also possible that during lower stimulation frequencies, flies may increase their levels of the recently hypothesized ‘active sleep’ state (inactivity of between 1 and 5 min in duration associated with physiological changes) ( Anthoney et al, 2023 ; Tainton-Heap et al, 2021 ) and that this may prevent the build-up of sleep pressure and rebound. We examined the levels of such sleep during and after deprivation using 220 s stimulation frequencies and found that the flies do display substantial increases in this short sleep state throughout deprivation using 220 s stimulation frequencies ( Figure 1—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…That is, the mechanical disturbance experienced by the sleep-deprived flies may produce effects on the fly that could obscure sleep-pressure-driven behavioral changes. Second, the 220 s inactivity triggers used to deprive flies of sleep may have allowed brief inactivity bouts recently hypothesized to represent an ‘active sleep’ state ( Anthoney et al, 2023 ; Tainton-Heap et al, 2021 ) and such a state prevented the build-up of sufficient sleep pressure to produce a homeostatic response. This would suggest that the 5 min inactivity criterion for sleep may be too long to capture all forms of homeostatically controlled fly sleep.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation